Education, Information Literacy and Lifelong Learning: Three Pillars of Nation Building in the Emerging Knowledge Society - Singh, Jagtar; Begum, Dilara (Bangladesh Journal of Library and Information Science, 2012)
This paper is based on the assumption that libraries have a pivotal role to play in nation building, and future of libraries is in our own hands. It further emphasizes the need for change in libraries in the context of emerging knowledge economy. It makes reference to the United Nations' Millennium Development Goals, UNESCO's Education for All Programme (EPAP), and Information for All Programme (IFAP), as well as the mandate of the National Knowledge Commission (NKC). It also highlights the impact of ICT on the life and work of people, and paradigm shift in libraries. It emphasizes that library consortia, institutional repositories, and open access archives are strategic response to the paradoxical situation of growing digital documents and declining library budgets. It further explains that more important than the name of a library (traditional or digital) is the mandate and the context of the library. It also enlists the challenges and opportunities facing libraries, and concludes that the future of libraries is though uncertain, yet in our own hands. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.48-56 DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12921